Design Thinking Approach in The Development of Cirgeo's World Media - Made Juniantari; Saida Ulfa; Henry Praherdhiono (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2023)
The circle concept is one of the contents in mathematics that has high complexity and is still a problem in visualization and concept exploration. This study aims to develop interactive digital media on circular material based on material characteristics, learning styles, user needs, and ease of learning in various contexts which are hereinafter named Cirgeo's World media. Media Cirgeo's World was developed using the design thinking method which has five stages, namely: 1) recognize and empathize; 2) defined; 3) ideate; 4) prototypes, and; 5) tests. Based on user responses obtained using questionnaires, the results obtained are that Cirgeo's World media is able to provide convenience for users in understanding learning objectives, learning by accommodating diverse learning styles, exploring abstract concepts more dynamically, measuring learning progress, and can be directly operated on the user's smartphone. From the results of user responses, it was also found that there were still things that were not optimal in Cirgeo's World media, namely in the user's ease of understanding the instructions for using the media. This can be followed up by improving things related to the instructions for using media that are easily accessible to users based on the results of interviews with users.